Seven-Tesla magnetization transfer imaging to detect multiple sclerosis white matter lesions - Chou, I-Jun; Lim, Su-Yin; Tanasescu, Radu; Al-Radaideh, Ali; Mougin, Olivier E.; Tench, Christopher R.; Whitehouse, William P.; Gowland, Penny A.; Constantinescu, Cris S. (SAGE Publications, 2017)
BACKGROUND AND PURPOSE: Fluid-attenuated inversion recovery (FLAIR) imaging at 3 Tesla (T) field strength is the most sensitive modality for detecting white matter lesions in multiple sclerosis. While 7T FLAIR is effective in detecting cortical lesions, it has not been fully optimized for visualization of white matter lesions and thus has not been used for delineating lesions in quantitative magnetic resonance imaging (MRI) studies of the normal appearing white matter in multiple sclerosis. Therefore, we aimed to evaluate the sensitivity of 7T magnetization-transfer-weighted (MTw) images in the detection of white matter lesions compared with 3T-FLAIR. METHODS:Fifteen patients with clinically isolated syndrome, 6 with multiple sclerosis, and 10 healthy participants were scanned with 7T 3-dimensional (D) MTw and 3T-2D-FLAIR sequences on the same day. White matter lesions visible on either sequence were delineated. RESULTS: Of 662 lesions identified on 3T-2D-FLAIR images, 652 were detected on 7T-3D-MTw images (sensitivity, 98%; 95% confidence interval, 97% to 99%). The Spearman correlation coefficient between lesion loads estimated by the two sequences was .910. The intrarater and interrater reliability for 7T-3D-MTw images was good with an intraclass correlation coefficient (ICC) of 98.4% and 81.8%, which is similar to that for 3T-2D-FLAIR images (ICC 96.1% and 96.7%). CONCLUSION: Seven-Tesla MTw sequences detected most of the white matter lesions identified by FLAIR at 3T. This suggests that 7T-MTw imaging is a robust alternative for detecting demyelinating lesions in addition to 3T-FLAIR. Future studies need to compare the roles of optimized 7T-FLAIR and of 7T-MTw imaging.